89Zr‐ and Fe‐Labeled Polymeric Micelles for Dual Modality PET and T1‐Weighted MR Imaging. Issue 14 (1st September 2015) - Starmans, Lucas W. E.; Hummelink, Marcus A. P. M.; Rossin, Raffaella; Kneepkens, Esther C. M.; Lamerichs, Rolf; Donato, Katia; Nicolay, Klaas; Grüll, Holger
Abstract : In this study, a new 89 Zr‐ and Fe 3+ ‐labeled micelle nanoplatform ( 89 Zr/Fe‐DFO‐micelles) for dual modality position emission tomography/magnetic resonance (PET/MR) imaging is investigated. The nanoplatform consists of self‐assembling amphiphilic diblock copolymers that are functionalized with 89 Zr‐deferoxamine ( 89 Zr‐DFO) and Fe 3+ ‐deferoxamine (Fe‐DFO) for PET and MR purposes, respectively. 89 Zr displays favorable PET imaging characteristics with a 3.3 d half‐life suitable for imaging long circulating nanoparticles. The nanoparticles are modified with Fe‐DFO as MR T1 ‐contrast label instead of commonly used Gd 3+ ‐based chelates. As these micelles are cleared by liver and spleen, any long term Gd‐ related toxicity such as nephrogenic systemic fibrosis is avoided. As a proof of concept, an in vivo PET/MR study in mice is presented showing tumor targeting of 89 Zr/Fe‐DFO‐micelles through the enhanced permeability and retention (EPR) effect of tumors, yielding high tumor‐to‐blood (10.3 ± 3.6) and tumor‐to‐muscle (15.3 ± 8.1) ratios at 48 h post injection. In vivo PET images clearly delineate the tumor tissue and show good correspondence with ex vivo biodistribution results. In vivo magnetic resonance imaging (MRI) allows visualization of the intratumoral distribution of the 89 Zr/Fe‐DFO‐micelles at high resolution. In summary, the 89 Zr/Fe‐DFO‐micelle nanoparticulate platform allows EPR‐based tumor PET/MRI, and, furthermore, holds great potential for PET/MR image guided drug delivery. Abstract : This study reports on a novel 89 Zr‐ and Fe‐labeled polymeric micelle nanoplatform ( 89 Zr/Fe‐DFO‐micelles) for bimodal positron emission tomography/magnetic resonance (PET/MR) imaging. 89 Zr/Fe‐DFO‐micelles clearly delineate tumor tissue in a tumor mouse model using PET/MR imaging. As the nanoparticles are modified with Fe‐deferoxamine instead of commonly used Gd 3+ ‐based chelates, any long term Gd‐related toxicity such as nephrogenic systemic fibrosis is avoided.